Radical Ecopoetics: The Apocalyptic Vision of Jorie Graham’s Sea Change - Ryoo, Gi Taek (Text Matters: A Journal of Literature, Theory and Culture, 2023)
Jorie Graham’s Sea Change (2008) addresses the environmental crisis engendered by climate change, sending us a dire warning of the end of humanity by featuring an apocalyptic world. Sea Change gives a poetic voice to the dynamics of climate change by embodying the catastrophe in linguistic forms and thus enabling us to experience the ecological crisis. For Graham, poetic imagination is an act of physical or bodily engagement as it brings together linguistic and emotional factors into an embodied performance. This paper explores the affective dimension of Graham’s experimental poetry to demonstrate how her radical ecopoetics allows us to (re)engage with the material world, and how it changes our perceptual and sensorial registers to awaken our sense of interconnectedness with nonhuman others.